CHARACTERISTICS OF THE ANTARCTIC OZONE HOLE DERIVED FROM NIMBUS 7 TOMS DATA - KRUEGER, Arlin J.; STOLARSKI, Richard S.; SCHOEBERL, Mark R. (National Institute of Polar Research, 1987)
P(論文) Global total ozone has been mapped with the Nimbus 7 Total Ozone Mapping Spectrometer (TOMS) instrument since November 1978. Very detailed daily maps are produced with this instrument which has a spatial resolution at nadir of 50km. The data accuracy is better than 2% under all weather conditions as evaluated by comparison with Dobson spectrophotometer network stations. Coverage is complete at all sunlit latitudes including the poles during non-polar night months. The general structure of southern hemisphere total ozone is a polar minimum surrounded by a circumpolar maximum. Over much of the year the gradients are quite small except for local midlatitude storms. However, during the spring months the difference between the minimum and the maximum grows with time. The boundary of the polar minimum is generally very sharp with a gradient of 10 Dobson units/100km not uncommon, thus justifying the term "ozone hole" to describe this feature. A station in the boundary region will undergo very large changes in ozone as the position of the hole drifts and fluctuates. Finally, the ozone hole is destroyed as the polar vortex breaks down in November. These characteristics were illustrated during the Symposium in a motion picture of daily ozone maps for a complete year. A second motion picture shows the striking decrease of Antarctic ozone during each of the October months since 1979 to values near 140 Dobson units, far below the lowest (180 Dobson units) ever observed previously at any location. It is this decrease which is the subject of the current controversy over possible fluorocarbon effects on ozone. The data from TOMS show that dynamics are critical in the formation of the ozone hole. Total ozone in the Antarctic region is found to be highly correlated with air temperature in the lower stratosphere. departmental bulletin paper